Perspectives of Teachers and Students on Values Education in Secondary School Religious Culture and Moral Knowledge Course - Seviye ARSLAN; Murat İNCE (Değerler Eğitimi Dergisi)
This research was carried out to evaluate the opinions of teachers and students on the values education taught in the secondary school Religious Culture and Moral Knowledge course. In this study, sequential descriptive pattern, one of the mixed method designs, was used. 315 secondary school students studying at seven different schools in the 2021-2022 academic year in Gerede and Dörtdivan districts of Bolu province participated in the study. Participants consisted of 162 female and 153 male students. In the research conducted, the opinions of 10 Religious Culture and Moral Knowledge (DKAB) teachers employed in the Ministry of National Education (MoNE) were sought. The study utilized the “Human Values Scale,” a tool developed for students, and a semi-structured “Teacher Interview Form” to collect data. The qualitative data was analyzed using descriptive analysis technique. According to the results of the research; it was found that student value levels were above average. It was also found that the students’ value levels indicated significant differences according to gender and grade. According to the teachers’ opinions on value education, they emphasized the importance of being role models in instilling values in students. Additionally, the teachers expressed concerns about the challenges posed by the unconscious use of technology and mass media in value education.